From Local Values to Universal Values: A Review to the Philosophical Values of Sasi Culture that Integrated with Moral Education for the Young Generation - Patty, Joice (Journal of Research and Investigation in Education, 2025)
This study endeavors to investigate the philosophical values inherent in the Sasi culture and to explore methodologies for integrating these values into character education for the younger generation. Sasi encompasses not only customary regulations and sanctions governing the management of natural resources but also embodies philosophical principles that significantly influence the character development of village communities. The advent of modernization has precipitated substantial transformations within community life, resulting in a discernible shift (deconstruction) in both the existence and the values associated with Sasi. Traditional elders, possessing a profound understanding of Sasi culture, are motivated to preserve and transmit these values to younger generations, recognizing that the philosophical tenets embedded within Sasi represent a legacy of ancestral wisdom that has been interwoven with character education in village life since time immemorial. The research methodology employed in this study is qualitative descriptive, encompassing literature reviews as well as unstructured data collection through interviews, observations, and interactive engagement. The findings indicate that the philosophical values intrinsic to the Sasi tradition are interpreted as noble principles that serve as foundational elements for the character formation of village communities. These values of local wisdom are actively nurtured and imparted by parents to the younger generation, as they are perceived to possess enduring relevance and universal applicability across diverse contexts.